Quincy's Market A Boston Landmark - Quincy, John, 1951-; Corbett, Hillary; Project Muse.; Project Muse. (2019)
A bustling commercial center and favorite tourist attraction on Boston's historic waterfront, Quincy Market, the popular name for Faneuil Hall Marketplace, draws throngs of visitors to the magnificent granite buildings and cobblestone concourses that house the area's specialty shops, restaurants, boutiques, pushcarts, and food stalls. Yet few are aware of the history of this legendary public place and its importance in the history of Boston and the nation. In this elegantly written and lavishly illustrated work, John Quincy, Jr., tells the absorbing story of the Market's unique evolution over the centuries. Beginning with John Winthrop's landing at the Great Cove on the Shawmut Peninsula in 1630, Quincy weaves together a remarkable tapestry of the district's rise, fall, and rebirth. Originally published by Northeastern University Press in 2003. With a new foreword by Hillary Corbett.
Divisions over a marketplace : From open fields to Faneuil Hall -- Faneuil Hall and the marketplace witness a revolution -- A need for renewal : Josiah Quincy proposes a new marketplace -- Negotiating for a grand market -- Building the new market -- Faneuil Hall market is born -- Quincy's Market : Decline and survival -- Rebuilding the markets -- Faneuil Hall marketplace : Sustaining the results.
Reprint of 2003 edition with new foreword.
Open access edition supported by the National Endowment for the Humanities / Andrew W. Mellon Foundation Humanities Open Book Program.
The text of this book is licensed under a Creative Commons Attribution-NonCommercial-No derivatives 4.0 International License
Includes bibliographical references (pages 268-274) and index.
Description based on print version record.
Keywords: Quincy's Market (Boston, Mass.); Quincy's Market (Boston, Mass.); Massachusetts -- Boston; Boston (Mass.) -- Economic conditions; Boston (Mass.) -- Buildings, structures, etc; Boston (Mass.) -- History; Markets -- Conservation and restoration; Economic history; Buildings; Architecture; Markets -- Conservation and restoration -- Massachusetts -- Boston; Architecture -- Massachusetts -- Boston; History; Electronic books; Electronic books